1994
DOI: 10.1016/0014-5793(94)80454-0
|View full text |Cite
|
Sign up to set email alerts
|

Both interleukin‐8 receptors independently mediate chemotaxis

Abstract: Neutrophil leukocytes, the target cells for interleukin-8 and related CXC chemokines, bear high numbers of two types of IL-8 receptors (IL-8Rl and IL-8R2). By cDNA transfection Jurkat cell lines were generated that stably express either IL-8Rl or IL-8R2 (J-IL8Rl and J-IL8R2). J-IL8Rl expressed 4,000 + 1,000 copies of IL-8R1, and bound IL-8 with high affinity (Kd l-4 nM) and GROcl and NAP-2 with low affinity (Kd 200-500 nM). J-IL8R2 expressed 17,000 f 3,000 copies of IL-8R2, and bound all three chemokines with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 35 publications
7
92
2
Order By: Relevance
“…Both cell lines were found to bind IL-8 with similar high affinity (Table 1), comparable with IL-8 binding to human neutrophils [7,9]. Although, Loetscher et al [20] previously demonstrated the migratory characteristics of Jurkat cells transfected with IL-8 receptors, other chemokine-induced neutrophil functions were not addressed. Here we were unable to detect IL-8 stimulation of superoxide production in our transfectants and Western blot analysis of Jurkat cell lysates confirmed the absence of p47-phox and p67-phox, cytosolic factors of the superoxide-generating NADPH oxidase, (data not shown).…”
Section: Characterisation Of Jurkat Transfectantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Both cell lines were found to bind IL-8 with similar high affinity (Table 1), comparable with IL-8 binding to human neutrophils [7,9]. Although, Loetscher et al [20] previously demonstrated the migratory characteristics of Jurkat cells transfected with IL-8 receptors, other chemokine-induced neutrophil functions were not addressed. Here we were unable to detect IL-8 stimulation of superoxide production in our transfectants and Western blot analysis of Jurkat cell lysates confirmed the absence of p47-phox and p67-phox, cytosolic factors of the superoxide-generating NADPH oxidase, (data not shown).…”
Section: Characterisation Of Jurkat Transfectantsmentioning
confidence: 99%
“…A 1,112 bp cDNA fragment encoding for IL-8R1 was generated as outlined by Leotscher et al [20] and sub-cloned into pcDNA-Y Briefly, 20/tg oflinearised pcDNA-3/IL-8R 1 was transfected into Jurkat cells (5-8 x 106 cells/800/.tl PBS) by electroporation. Two weeks later G418-resistant (0.8 mg/ml) Jurkat clones were selected by limited dilution and characterized for expression of IL-8R 1 by ~25I-IL-8 binding.…”
Section: Preparation Of Jurkat Transfectants Expressandg Either Il-8r1 Ormentioning
confidence: 99%
See 3 more Smart Citations